Tuberculous Meningitis: The Microbiological Laboratory Diagnosis and Its Drug Sensitivity Patterns - Titiek Sulistyowati; Deby Kusumaningrum; Eko Budi Koendhori; Ni Made Mertaniasih (Faculty of Medicine Universitas Airlangga, 2017)
Background: Tuberculosis continues one of the major challenges to global health. Mycobacterium tuberculosis complex can affect any organ other than the lung parenchyma, include central nervous system. The mortality rate of tuberculous meningitis (TBM) are high worldwide with up to half of survivors suffering irreversible sequelae. Diagnosis of TBM is difficult due to paucibacillary, various clinical manifestation, and invasive procedure to appropriate specimens. Objective: The objectiveis to study the positivity rate of microbiological laboratory diagnosis and its drug sensitivity patterns of TBM patients in Dr. Soetomo Hospital Surabaya during October 2015 until September 2016. Methods: Specimens were cerebrospinal fluids. Identification and drug anti TB sensitivity test were done by BACTEC MGIT 960 system in Clinical Microbiology Laboratory Dr. Soetomo Hospital Surabaya. Result: Most patients with TBM were women (54.29%). Based on age groups, most dominant was adult population (65.71%). Proportion percentage of positive M. tuberculosis complex among 180 specimens were 19.44%. First line anti TB drug sensitivity pattern of 35 isolates were 1 monoresistant, 1 poly-resistant, no multiple drug resistant (MDR), and 33 pan-susceptible. Conclusion: Positivity rate of Mycobacterium tuberculosis complex laboratory diagnosis from TBM suspect patients were low. There was no MDR TB in this study, but mono-resistant and poly-resistant. Microbiological diagnosis was important to give information of active disease and drug sensitivity pattern. Resistance to first line anti TB drugs is alarming to properly manage TBM patients.